Beyond Business-as-Usual: Achieving a Paradigm Shift towards Low-Carbon Transport - Zachariadis, Theodoros (My University, 2012)
Transportation is responsible for a continuously rising share of global carbon emissions. Carefully designed regulations, supported by land use strategies, fiscal policies and local incentives, and enabled through targeted international development assistance, can reverse these unsustainable trends.
Keywords: Transportation; Low-Carbon Transport; Global Carbon Emissions